Pengaruh Inflasi, Suku Bunga dan Nilai Tukar terhadap Harga Saham Dengan Pertumbuhan Ekonomi Sebagai variabel intervening pada perusahaan sektor Healthcare di Bursa Efek Indonesia (MOTIVASI, 2023)
Purpose – This study aims to determine the effect of Inflation, Interes Rates and Exchange Rates on Stock Prices with Economic Growth as an intervening variable in healthcare sector companies on the indonesian stock exchange.  Design/methodology – This research is a quantitative approach, there is data calculation in the form of numbers. The research population used 25 healthcare companies listed on the IDX for the 2014-2021 period. Using purposive sampling techniques, 11 sample companies were obtained during the 2014-2021 period. Technique data analysis used is Structural Modeling Equation (SEM) with Program IBM SPSS AMOS 24. Findings - The result show that Inflation affected Economic Growt, Interest Rate did not affect Economic Growth, Exchange affected Economic Growth, Inflation affected The Stock Price, Interest Rates did not affect The Stock Price, Exchange Rates affected The Stock Price, Economic Growth did not affect The Stock Price, Economic Growth strengthens the influence of Inflation on The Stock Price, Economic Growth strengthens the influence of Interest Rate on The Stock Price, Economic Growth strengthens the influence of Exchange Rate on The Stock Price.